Gastro-intestinal complications as one of causes of death in patients with rheumatic diseases - V N Sorotskaya; A E Karateev (Научно-практическая ревматология, 2005)
Objective. To assess frequency of gastro-intestinal (Gl) bleeding and ulcer perforation as direct cause of death in pts with rheumatic diseases. Material and methods. Statistical analysis of Tula region patient care institutions documentation was performed to assess frequency and character of severe GI complications leading to death of pts. 300 cases of death which took place during 5 years (1996-2000) in 3 rheumatologic (105 cases) and 10 therapeutic (195 cases) departments of Tula region patient care institutions were studied. Results. Gl bleeding and ulcer perforation were the direct causes of death in 15 pts with rheumatic diseases i.e. in 5% from the whole number of died. GI complications caused death in 4 pts with chronic rheumatic heart disease (HRHD) (1,7%), in 7 (15,2%)with rheumatoid arthritis -, in 2 with ankylosing spondylitis and systemic lupus erythematosus (8,0 and 22,2% respectively). Pts with systemic sclerosis did not die because of GI damage. GI changes most frequently localized in duodenum (8 pts). 4 pts had complications connected with gastric ulcer and in 2 diffuse erosive damage of Gl mucosa was the source of bleeding. Conclusion. Severe Gl complications quite often lead to death of pts with rheumatic diseases in Tula region.